The technological tools use in education: Turkish electric teacher's candidates' ideas - (:unkn) unknown (DRUNPP-SARAJEVO, 2012)
Our era is captive of technology that symbolizes velocity and advancement. This incredible advancement of technology affects our life standard positively. Views of candidates for being Electrical Teacher who has an important part transferring of this advancement to humans are explored in this study. Sample of this research consist of 99 students of Electrical Education Department, Technical Education Faculty of three different universities at different semesters, in 'other words 99 candidates for being Electrical Teacher. Frequency, percentage, t-test and Anova statistical methods are used for data analyze. Differences are seen about technological tools usage according to working desire on own education areas in future, age, their universities, semester and mother education status variables.
Keywords: Technological tools; education; Anova statistical method; Electric Education Teachers